Does Accelerometer-based Navigation Have Any Clinical Benefit Compared with Conventional TKA? A Systematic Review. Issue 9 (September 2019) - Budhiparama, Nicolaas C.; Lumban-Gaol, Imelda; Ifran, Nadia N.; Parratte, Sebastien; Nelissen, Rob
Abstract: Background: Accelerometer-based navigation is a handheld navigation tool that was introduced to offer a simpler technique compared with more-cumbersome computer-assisted surgery (CAS). Considering the increasing number of adopters, it seems important to evaluate the potential clinical benefits of this technology compared with conventional TKA. Questions/purposes: In this systematic review, we asked: (1) Is accelerometer-based navigation more accurate than conventional TKA? (2) Does accelerometer-based navigation provide better functional outcome than conventional TKA? (3) Does accelerometer-based navigation increase surgical time or decrease the risk of complications or reoperations compared with conventional TKA? Methods: This systematic review included all comparative prospective and retrospective studies published in the MEDLINE/PubMed and Cochrane libraries over the last 10 years. Inclusion criteria were all studies in English that compared accelerometer-based navigation with conventional TKA. Eleven studies met these criteria with 621 knees in accelerometer-based navigation group and 677 knees in conventional TKA group. Results related to alignment, objective and subjective functional scores, duration of surgery, complications and reoperations were extracted and compared between accelerometer-based-navigation and conventional TKA. Methodological quality was assessed using Methodological Index for Non-Randomized Studies (MINORS) tool (for nonrandomized control trials) and Cochrane Risk of Bias (for randomized control trials (RCTs). All studies with fair or better quality were included. Four RCTs and six nonrandomized studies comparing accelerometer-based navigation to conventional TKA were found. Results: Inconsistent evidence on mechanical axis alignment was found, with five of nine studies slightly favoring the accelerometer-based navigation group, and the other four showing no differences between the groups. Only two of eight studies favored accelerometer-based navigation in terms of tibial component alignment in the coronal plane; the other six found no between-group differences. Similarly, mixed results were found regarding other metrics related to component alignment; a minority of studies favored accelerometer-based navigation by a small margin, and most studies found no between-group differences. Only three studies evaluated functional outcome and none of them showed a difference in range of motion or patient-reported outcomes. Most studies, six of seven, found no between-group differences concerning surgical time; one study demonstrated a slight increase in time with accelerometer-based navigation. There were no between-group differences in terms of the risk of complications, which generally were uncommon in both groups, and no reoperations or revisions were reported in either group. Conclusions: We found conflicting evidence about whether accelerometer-based navigation reduces the number of coronal-plane outliers or improves alignment to a clinically important degree, and we found no evidence that it improves patient-reported outcomes or reduces the risk of complications or reoperations. Accelerometer-based navigation may increase surgical time. The overall quality of the evidence was low, which suggested that any observed benefits were overestimated. Given the absence of higher-quality evidence demonstrating compelling benefits of this accelerometer-based navigation technology, it should not be widely adopted. Level of Evidence: Level III, therapeutic study.